Chemical analysis of Hg0-containing Hindu religious objects. - Adam M Kiefer; Caryn S Seney; Evelyn A Boyd; Caroline Smith; Darran S Shivdat; Elaina Matthews; Michael W Hull; Christy C Bridges; Amber Castleberry (PLoS ONE)
Parad items used in Hindu practices and Ayurvedic medicines contain elemental mercury (Hg0) and have traditionally been used in prayer and to treat a variety of diseases including diabetes, heart conditions, and sexual dysfunction. These items are often referred to as amalgams of silver, and take the form of shivlings, statues of gods, necklaces, and other jewelry. Fourteen parad items were purchased from online vendors in India and the United States and analyzed. All items produced copious amounts of Hg0 vapor, with Hg0 concentrations exceeding 1,000,000 ng/m3 as measured using a Mercury Instruments Mercury Tracker 3000 IP atomic absorption spectrometer. Measured concentrations were highly variable, so a simple qualitative experiment employing a UV-C light source and a thin-layer chromatography plate impregnated with a fluorescent dye that glows green when irradiated at 254 nm allowed for the indirect visualization of the Hg0 being evolved. In addition, all items were screened using a hand-held X-ray fluorescence analyzer to estimate the concentration of Hg, Sn, Pb, As, and Cd on the surface of the item. Select samples were then digested in aqua regia and analyzed for Hg content using a direct mercury analyzer. All samples were found to exceed 20% by mass Hg. The digestates were analyzed using inductively-coupled plasma-optical emission spectrometry and were determined to be between 10-55% by mass Pb and contain up to 0.3% by mass As. While Article 4 of the Minamata Convention on Mercury specifically requires parties to stop importing, exporting, and manufacturing Hg-added products, products used in traditional and religious practices are excluded.